Wavelet based multicarrier CDMA system - Nasser Hamad; Maen Takruri; Mahdi Barhoush (International Journal of Electrical and Computer Engineering (IJECE), 2019)
Emerging demands for high data rate services, high user capacity and low power consumption systems are the key driving forces behind the continued technology evolution in wireless communications. Multicarrier Modulation techniques support variety of services requiring different data rates and different QoS (quality of service) levels. Multicarrier CDMA is a wireless communication system that can be seen as a combination of direct sequence CDMA and Orthogonal Frequency Division Multiplexing techniques. The main benefits of this system are its robustness to inter symbol interference and multipath propagation in fading channels. This paper studies and simulates the Discrete Wavelet Transform based Multicarrier CDMA and compares it with the  Discrete Fourier Transform based one using different number of sub carriers, and different modulation techniques. The results shows that the Wavelet based system outperforms the Fourier based one since it has lower bit error rate BER performance, lower peak to verage power ratio PAPR and higher user capacity.